Recent advances in bio-electrochemical system analysis in biorefineries. Issue 5 (October 2021) - Siwal, Samarjeet Singh; Zhang, Qibo; Saini, Adesh Kumar; Gupta, Vijai Kumar; Roberts, Dave; Saini, Vipin; Coulon, Frederic; Pareek, Bhawna; Thakur, Vijay Kumar
Abstract: Concerns around acquiring the appropriate resources toward a growing world population have emphasized the significance of crucial connections between food, energy, and water devices, as described within the food-energy-water nexus theory. Advanced biorefineries provide second-generation biofuels and added-value chemicals through food products have affected these nexus sources. We combine various conversion technologies and expected options to look further for cost-effective technologies that maximize the value of resource use and reuse and minimize the amount of resource needed and environmental impacts. In this review article, our central focus is on structure and application, the outline of food-energy-water (FEW) nexus in biorefineries and bio-electrochemical system (BES) and looking into the energy-efficient and value-added product recovery. In addition, based on BES analysis for energy efficiency and valuable product recoveries such as hydrogen evaluation, acetate, recovery of heavy metals, nutrient's recovery has been discussed under this article. Additionally, we focused on wastewater processing methods, novel electrode materials used in BES, BESs-based desalination and wastewater treatment, recent BES architecture and designs, genetic engineering for enhanced productivity, and valuable materials production surfactants and hydrogen peroxide. Finally, we concluded the topic by discussing the remediation of soil contamination, photosynthetic & microfluidic BES systems, possibilities of employing CO2, including prospects and challenges. Graphical Abstract: ga1 Highlights: Bio-electrochemical systems (BESs) in Biorefineries, mechanism and their types. Structure and applications of FEW nexus of biorefinery and bio-electrochemical system. Types and significance of bio-electrochemical systems. Bottlenecks associated with BES are discussed. Conferred future challenges to develop research interest in BESs.